Impact of Alkaline Pretreatment to Enhance Volatile Fatty Acids (VFAs) Production from Rice Husk - Qian Fang; Sinmin Ji; Dingwu Huang; Zhouyue Huang; Zilong Huang; Yunyi Zeng; Yu Liu (Biochemistry Research International)
This study explores the use of alkaline pretreatments to improve the hydrolyzation of rice husks to produce volatile fatty acids (VFAs). The study investigated the effects of reagent concentration and pretreatment time on protein, carbohydrates, and dissolved chemical oxygen demand (SCOD) dissolution after the pretreatment. The optimum alkaline pretreatment conditions were 0.30 g NaOH (g VS)−1, with a reaction time of 48 h. The experimental results show that when comparing the total VFA (TVFA) yields from the alkaline-pretreated risk husk with those from the untreated rice husk, over 14 d and 2 d, the maximum value reached 1237.7 and 716.0 mg·L−1 with acetic acid and propionic acid and with acetic acid and butyric acid, respectively. After the alkaline pretreatment, TVFAs increased by 72.9%; VFA accumulation grew over time. The study found that alkaline pretreatment can improve VFA yields from rice husks and transform butyric acid fermentation into propionic acid fermentation. The study results can provide guidelines to support the comprehensive utilization of rice husk and waste treatment.